0800 Dozing off is a problem, as is a toe falling off - Methylphenidate induced Raynaud's phenomenon. (25th May 2022) - Gaddam, Maneesh; Zacharias, Rajesh; He, Wei; Oster, Joel; Ostrow, Peter; Schumaker, Greg; Grover, Aarti
Abstract: Introduction: Narcolepsy is a clinical syndrome characterized by a constellation of symptoms including excessive daytime sleepiness, cataplexy, sleep paralysis and sleep hallucinations. Stimulants are commonly used to treat hypersomolence associated with narcolepsy. Common adverse reactions reviewed with patients prior to initiation of amphetamines include decreased appetite, nausea, xerostomia, headache, insomnia, tachycardia and hypertension. A relatively rare concern with stimulants is development of peripheral vasculopathy including Raynaud's phenomenon. Report of Cases: A 25-year-old female with past medical history of anxiety, depression and obstructive sleep apnea in childhood was treated with tonsillectomy and adenoidectomy. Over the years, she continued to have persistent hypersomnolence, auditory hypnogogic hallucinations with no symptoms of sleep paralysis or cataplexy. She had a polysomnography (PSG) along with multiple sleep latency test (MSLT). PSG did not show evidence of sleep apnea with an AHI of 0.96 per hour. MSLT confirmed the diagnosis of Narcolepsy, Type 2, with a mean sleep onset latency of 3.6 minutes and five sleep-onset REM periods (SOREMPs). She was started on 400mg daily of Modafinil and 20mg daily of Methylphenidate. After a month of using methylphenidate, she noticed purplish discoloration of her digits, sometimes with exposure to cold, other times with no obvious triggers, consistent with development of Raynaud's phenomenon. The proposed mechanism is that use of methylphenidate causes excessive release of catecholamines due to inhibition of the reuptake of dopamine and norepinephrine, leading to peripheral vasoconstriction. As the patient's hypersomnolence persisted, she was started on sodium oxybate and the dosage of methylphenidate was decreased to 10mg daily and eventually discontinued. With reduction in the dosage and discontinuation of methylphenidate, symptoms of Raynaud's phenomenon improved. Conclusion: Dose-related peripheral vasculopathy including Raynaud's phenomenon has been reported in several case reports with the use of methylphenidate. Awareness of this relatively rare adverse effect is imperative among sleep physicians as it could cause significant delay in the diagnosis, management of Raynaud's phenomenon and its complications including critical digital ischemia and gangrene. Dose adjustments and discontinuation of methylphenidate should be considered in the treatment course of the patients with such concern. Support (If Any):